Distribuição do ictioplâncton no reservatório de Rosana, rio Paranapanema, Brasil. - Kipper, Darlon (2010)
The knowledge of forces that determine the ichthyoplankton spatial-temporal organization in reservoir can be valuable to predict and understand the fish recruitment, supporting the environmental management projects. This study intends to evaluate the spatial distribution and relate the abundance with abiotic factors, as well as identify larval and verify if the assemblage presents an organization different of the random. Samples were quarterly in 2002, in limnetic and littoral regions of Rosana reservoir. Differences in the spatial variation of larvae were evaluated by Kruskal-wallis test. Principal Components Analyses, ANOVAs and Spearman correlation were applied to relate total larval density and biotic and abiotic variables in limnetic region. To verify the assemblage spatial organization, was applied a co-occurrence null model. It was captured 55 eggs and 895 larval, and in limnetic region, the larval appeared almost exclusively in December. This region presented significant differences, with Plagioscion squamosissimus and Hypophthalmus edentatus dominance. In littoral region, larval was distributed in March and December, and this region not presented significant differences, prevailing Bryconamericus stramineus. The limnetic region larval was directly related with water temperature, pH and dissolved oxygen and also with zooplankton. The null models showed that larval assemblages were segregated in high precipitation period. Limnetic and littoral regions of the reservoir, as well as their respective zones showed differences in species composition of larvae and segregation of assemblages can be influenced by a preference for habitats or evolutionary questions involving reproductive strategies of species.